A needs analysis of an employee wellness programme : the case of the Financial Services Regulatory Authority (FSRA) of Swaziland - Madlopha, Sboniso Charles (Rhodes University, Faculty of Commerce, Rhodes Business School, 2015)
In 2010, the Financial Services Regulatory Authority (FSRA) of Swaziland noticed a significant increase in employee absenteeism which they discovered was related mainly to: poor health (sick leave), personal and financial stress (garnishee orders were increasing), and low staff morale, the consequence of which was low productivity and missed deadlines (FSRA, 2010:7). High levels of absenteeism meant that a sizeable number of employees were unable to complete their daily tasks (FSRA, 2010:7). Consequently, in 2011, the FSRA Human Resource Department started a wellness programme for all employees in the organization in an attempt to respond to the human resource challenges reported in 2009/10 financial year. By the end of 2012, FSRA management reported that the introduction of the EWP had not yielded the expected results. This therefore prompted management to request an evaluation of the FSRA employee wellness programme. The aim of this research was to identify and prioritize the needs of employees in terms of requirements of a wellness programme and how it should be delivered. The specific objectives of the study are as follows: to identify the wellness needs of employees, to identify employee preferences in terms of the type of interventions to be included in a wellness programme, to identify the preferred mode of delivery of the wellness programme and to make recommendations to management on the design of a wellness programme. Questionnaires with closed ended questions were used to collect data for this survey. The questionnaire used is attached as Appendix A. By means of a needs analysis survey, this research was designed to assess the FSRA employees' needs in terms of an employee wellness programme, as well as the preferred EWP delivery methods. About 70 percent of FSRA employees participated in the survey. The respondents completed the questionnaire and submitted it online over a period of 10 working days (2 weeks). This report is structured into three sections, namely; section one, which is the evaluation report that gives details of the importance of the study, highlights research methods and then present the results, discussions and recommendations. Section two deals with the literature review while section three reports on the research methodology, research design and procedures and the limitation of the study. In light of the findings on the wellness needs of employees, 72 percent of the respondents felt the current wellness programme was very inadequate and a further 10 percent added that it was inadequate in addressing their wellness needs largely because the needs were not known. The most important wellness needs identified included: exercise, nutrition, personal hygiene, disease awareness and treatment of illness, coping with stress, coping with workload, ventilation, safety, bereavement, personal debt, and retirement planning. The most preferred wellness interventions that respondents proposed include Flexible Work Schedule, Safe Workplace, Improved Ventilation, Retirement Planning Advice and Gymnasium. Further analysis done using correlation analysis indicated that there was a significant positive relationship between the wellness needs and the wellness interventions. Concerning the delivery of the wellness programme, most of the employees indicated that outsourcing certain services was better than having them in house. The highest ranking of the services for out sourcing were nutrition education and medical checkups that ranked between 82 percent and 75 percent respectively. The respondents indicated that they want almost all the chosen interventions to be outsourced. Time slots should also be taken into consideration to ensure employee participation in the wellness programme services. The respondent FSRA employees seem to prefer interventions of an educational nature to be during the lunch hour. These include Nutrition Education, Health Education, Hygiene Education and Medical Check ups and Treatment, whereas Gymnasium was preferred to be after working hours.
Keywords: Financial Services Regulatory Authority (Swaziland); Employee health promotion -- Swaziland; Needs assessment -- Swaziland; Absenteeism (Labor) -- Swaziland; Employee morale -- Swaziland; Contracting out -- Swaziland